ANALISIS KINERJA KEUANGAN PADA PT. SUMBER ALFARIA TRIJAYA TBK. YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Asnidar, Asnidar (Universitas Muhammadiyah Parepare, 2021)
This research aimed to determine the financial performance of PT. Sumber Alfaria Trijaya Tbk. 2017 to 2020 period with the parameters of the liquidity ratio, solvency ratio, and profitability ratio. This research used descriptive with a quantitative approach with a population of 2017-2020 financial statements. The liquidity ratio is measured by the current ratio and quick ratio, the solvency ratio is measured by debt to asset ratio and debt to equity ratio, while the profitability ratio is measured by return on equity and return on assets. The results of research with liquidity ratios show that the company is in an unhealthy condition, which is below 2 times for the current ratio and 1.5 times for the quick ratio. Based on the results of the solvency ratio analysis, it shows an unhealthy condition because the ratio is above the industry standard of 0.35 for the debt to asset ratio and 0.66 for the debt-to-equity ratio. Based on the results of the profitability ratio analysis, the results show that the return on equity is an average of 7.35% with an industry standard of 40% and an average return on assets of 2.03%, which is far below the 30% standard.